Risk by indication for pancreaticoduodenectomy in patients 80 years and older: a study from the American College of Surgeons National Surgical Quality Improvement Program. Issue 11 (November 2016) - Bergquist, John R.; Shubert, Christopher R.; Ubl, Daniel S.; Thiels, Cornelius A.; Kendrick, Michael L.; Truty, Mark J.; Habermann, Elizabeth B.
Abstract: Background: Expected mortality after elective pancreaticoduodenectomy (PD) in contemporary series is less than 5% in elderly patients; however, to our knowledge, mortality rate has not been correlated with indication for PD. We hypothesized that perioperative risk following PD would correlate with diagnostic indication in older patients. Methods: The American College of Surgeons NSQIP database was reviewed to identify patients (<80 and ≥80 years) who underwent PD from January 1, 2005, through December 31, 2012. High- and low-risk diagnoses were determined by using 30-day, major-morbidity data. Univariate and multivariable analyses were used to compare outcomes. Results: Pancreatic cancer and chronic pancreatitis were found to be low-risk diagnoses in elderly patients, whereas bile duct and ampullary neoplasm, duodenal neoplasm, and neuroendocrine tumors were high-risk diagnoses. The risk of 30-day mortality for older patients (≥80 y) undergoing PD was 6.1% for those with high-risk diagnoses vs 4.5% for those with low-risk diagnoses ( P  = .27). On multivariable analysis (controlling for confounders), a high-risk diagnosis was shown to be an independent predictor of prolonged length of stay, superficial surgical-site infection (SSI), and organ-space SSI. There was no increased risk of complications in patients ≥80 years with low-risk diagnoses. Conclusion: In patients 80 or older undergoing PD, perioperative risk varies by diagnostic indication. Patients should receive preoperative counseling about their risk.